2008
DOI: 10.1080/15205430802071258
|View full text |Cite
|
Sign up to set email alerts
|

From Self-Enhancement to Supporting Censorship: The Third-Person Effect Process in the Case of Internet Pornography

Abstract: This study examined the relationship between self-enhancement and third-person perception. It also investigated the behavioral consequences of third-person perception within a theory of reasoned action framework. A survey on the issue of Internet pornography was administered to 462 undergraduate students. A positive relationship was found between self-enhancement and third-person perception. Behavioral attitude emerged as a key mediator in the relationship between thirdperson perception and intention to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 58 publications
1
35
1
4
Order By: Relevance
“…For some of our participants, a tension was evident as they endorsed an optimistic bias (Cho, Lee, & Chung, 2010): These young people reported that they only accepted friend requests from people they know and then went on to describe how many of their friends/followers were unknown to them. The optimistic bias is predicated on an individual's belief that Running head: YOUNG PEOPLE'S TECHNOLOGY USE 20 compared to others they are at less risk of negative events (Zhao & Cai, 2008). Associated with an optimistic bias is the third person effect.…”
Section: Vulnerabilitymentioning
confidence: 99%
“…For some of our participants, a tension was evident as they endorsed an optimistic bias (Cho, Lee, & Chung, 2010): These young people reported that they only accepted friend requests from people they know and then went on to describe how many of their friends/followers were unknown to them. The optimistic bias is predicated on an individual's belief that Running head: YOUNG PEOPLE'S TECHNOLOGY USE 20 compared to others they are at less risk of negative events (Zhao & Cai, 2008). Associated with an optimistic bias is the third person effect.…”
Section: Vulnerabilitymentioning
confidence: 99%
“…Arguably, much of the negative attention that internet pornography has received could be attributed to third-person effects, wherein individuals believe strongly in the negative effects of internet pornography on others (Lee & Tamborini, 2005;Zhao & Cai, 2008). Such a contention is particularly supported by the body of literature suggesting that beliefs regarding the addictive nature of pornography seem to be particularly endemic in conservative religious subcultures, which often have specific prohibitions against pornography use (MacInnis & Hodson, 2016;Thomas, 2016;Thomas, Alper, & Gleason, 2017).…”
Section: Problematic Pornography Usementioning
confidence: 99%
“…The marketing literature has used it to model consumer behavior (George, 2002;Lim & Dubinsky, 2005). In communication science the theory has mostly been applied in relation to media effects (Golan & Banning, 2008;Zhao & Cai, 2008) and theories of media diffusion and usage (Rossmann, 2010, pp. 36ff.).…”
Section: Drivers Of Online Campaigningmentioning
confidence: 99%